Determinants of incorrect inhaler technique in chronic obstructive pulmonary disease patients. Issue 6 (12th February 2021) - Harb, Hadeer S.; Ibrahim Laz, Nabila; Rabea, Hoda; Abdelrahim, Mohamed E. A.
Abstract: Aims: There is a lack of an overview of determinants of incorrect inhaler technique among chronic obstructive pulmonary diseases (COPD) subjects. The aim of this study was to determine the prevalence and possible determinants of incorrect inhaler technique in COPD subjects with common inhalers. Methods: A cross over study was conducted in 180 COPD subjects. Baseline assessment of inhaler technique was evaluated in 10 placebo inhalers including: [pressurised metered dose inhaler (pMDI), Aerolizer, Handihaler, Turbohaler, Discus, Breezhaler, Ellipta, Easyhaler, Diskhaler and Respimat] without receiving any instructions. Subjects were then crossed over to other inhalers in random order. Inhaler technique was assessed. The proper technique of inhalers was demonstrated and the number of counselling attempts needed to achieve a correct technique was recorded. Patient past‐experience, demographics/clinical variables were recorded. Results: Incorrect inhaler techniques were highly prevalent among COPD subjects, ranging from 80% of participants demonstrated incorrect use, a minimum of 1 error, with Ellipta, to 100% with Respimat/Diskhaler ( P  < .001). Past‐experience (OR = 14.639 at P  < .001) and inhaler‐type (OR = 10.397 at P  < .001, 4.267 at P  =. 007, 2.664 at P  =. 057, 8.666 at P  =. 001, 10.250 at P  < .001, 0.613 at P  =. 212 and 0.265 at P < .001 for pMDI, Aerolizer, Handihaler, Turbohaler, Discus, Breezhaler and Ellipta, respectively) were the strongest determinants of incorrect technique followed by gender (OR = 0.310 at P  < .001), age category (OR = 0.307 at P  < .001) and GOLD group (OR = 2.289 at P  =. 005). Conclusion: Incorrect inhaler techniques are highly prevalent among COPD subjects. Lack of past‐experience, certain inhaler types, female gender, older age and lower GOLD group are the most significant determinants of incorrect technique.